Wiley Encyclopedia of Management 2015
DOI: 10.1002/9781118785317.weom110022
|View full text |Cite
|
Sign up to set email alerts
|

Environmentally Sustainable Work Behavior

Abstract: Promoting environmentally sustainable work behavior has rapidly increased as an area of interest in recent years for Organisational Behavior (OB) scholars. This article summarizes how the field has emerged from the broader sustainability agenda, describes the most influential theories and discusses the behavioral techniques employed in intervention studies. Major challenges and opportunities for research into environmentally sustainable work behavior are identified in particular, the need to integrate the dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 12 publications
0
16
0
1
Order By: Relevance
“…UK Parliamentary Office for Science and Technology, 2010). However, whilst changing individual behavior and every day practices has been the underlying philosophy behind many environmental behavior change programs outside of organizations (Uzzell and Moser, 2009), the role of employee behavior in delivering improvements in environmental performance within organizations has generally been overlooked (Ones and Dilchert, 2012;Davis and Challenger, 2013;). Further still, the role of HRM practices in influencing employee environmental behavior and subsequent EMS objectives has similarly been under-researched; this is despite researchers highlighting the potential role HRM could play in developing strategies for this purpose (e.g.…”
Section: Human Resource Management (Hrm) Is Likely Integral To Succesmentioning
confidence: 99%
“…UK Parliamentary Office for Science and Technology, 2010). However, whilst changing individual behavior and every day practices has been the underlying philosophy behind many environmental behavior change programs outside of organizations (Uzzell and Moser, 2009), the role of employee behavior in delivering improvements in environmental performance within organizations has generally been overlooked (Ones and Dilchert, 2012;Davis and Challenger, 2013;). Further still, the role of HRM practices in influencing employee environmental behavior and subsequent EMS objectives has similarly been under-researched; this is despite researchers highlighting the potential role HRM could play in developing strategies for this purpose (e.g.…”
Section: Human Resource Management (Hrm) Is Likely Integral To Succesmentioning
confidence: 99%
“…Pollution of water, land, and air resources has accelerated in recent years, which causes difficulties for individuals, organizations. and society as a whole [53]. At the same time, there has been a dramatic decrease in the availability of natural resources [54].…”
Section: Employee Sustainability Behaviormentioning
confidence: 99%
“…Finally, the present research has demonstrated that organizations should be mindful of the importance of involving workers in designing sustainability-oriented policy measures as a necessary element in the effectiveness of organizational social responsibility plans. The contribution that individual workers can make through engaging in environmentally sustainable workplace behavior has been underrepresented (Davis & Challenger, 2015), and employees perceive their suggestions for environmental improvement to be insufficiently considered (Dumitru et al, 2016). While individual behavior is constrained by organizational structures and formal and informal rules, it is still the case that people bring with them their values, identities, personal norms, and patterns of behavior, which have an influence on their interactions with others and their adaptation at the organizational structures and culture they find in place.…”
Section: Discussionmentioning
confidence: 99%
“…Although service-providing organizations have lower environmental impacts than industrial or manufacturing firms, changing the behavior of employees has the potential of achieving highly significant improvements in the overall environmental performance of the organization, including reductions in emissions. Research on the potential of organizational behavioral change policies to achieve significant emissions reductions is still scarce (Lo, Peters, & Kok, 2012), and the impact and contribution that individual workers can make in terms of improving an organization’s environmental performance through engaging in environmentally sustainable workplace behavior have been underrepresented (Davis & Challenger, 2015).…”
Section: Introductionmentioning
confidence: 99%